A study of language attitudes through English accent evaluations by Koreans in the Philippines - Roh, Teri Rose Dominica G. (2010)
The current shift of the status of English from a foreign language to a global language (Chang, 2008) facilitates the proliferation of general and unique attitudes towards speakers of English with various accents. Employing a model of accent evaluation adapted from Street and Hopper (1982), this study describes which attitudes are prevalent among Koreans currently studying English in the Philippines based on the evaluations they hold in relation to speakers with an American English accent (AmE), a Philippine English accent (PhilE), and Korean-accented English (KorE). The discussions include a holistic set of language attitudes that represent affective, behavioral, and cognitive outcomes (Ryan, et al., 1982). The evaluations of the three English accents were gathered from 120 teenage and adult Koreans staying in the Philippines during the survey period from December 2009 to January 2010. Direct and indirect techniques in eliciting language attitudes were utilized in designing the four key tasks in the questionnaire (i.e., perception of phonological features, categorization of the speaker, making judgments about the characteristics of the speaker, and evaluation through expression of preference). The findings indicate that Koreans show positive attitudes in responding to the tasks related to the speaker of AmE, while they hold neutral and negative language attitudes towards the speakers of the PhilE and KorE varieties, respectively. By implication, such attitudes invite English language teaching professionals, policy-makers, and concerned individuals to re-assess their current practices in order to uplift the status of stigmatized but equally important language varieties in the context of South Korea and similar contexts where English language learners expect to be able to understand the speech of other speakers of English as they, in turn, continuously strive to speak with an improved level of intelligibility.
Thesis (M.A. English Studies)--University of the Philippines, Diliman.
Keywords: English language -- Pronunciation by foreign speakers; Oral communication -- Philippines; Koreans -- Philippines